Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 19. 9% to 21% and that, over the 19 years between the two wars, it averaged 13½ %. (60) On this same subject, the Government Actuary, in his Memorandum (page 165), states that, in basing his financial calculations on Sir William's estimate of 10% as the likely unemployment figure after this war, he recognises that it is "highly speculative" and makes the following statement :- "I have consulted Sir William Beveridge on this and he is of opinion that it would be reasonable in the circumstances which he envisages in the Report to contemplate an average rate of unemployment of the order of 10% among the industries at present covered by the general scheme of Unemployment Insurance". (61) Sir William himself does not state in his Report on what factors his opinion is based but when, in his public speeches since the issue of his Report, he has addressed himself to this vital question, he is reported in the "Times" of 7th December as having said at Oxford :- "If we have mass unemployment we may not be able to carry out the proposals in my Report. We may give people the money but there will not be the goods for them and so there will be want. I do not know how we shall continue productive employment after the war. When people say we cannot abolish unemployment, however, I say we have abolished it twice in my lifetime - during the last war and during this war. I simply will not believe that it is impossible to abolish mass unemployment but I do not know how it is to be done and I do not know whether anybody else knows". (62) With the utmost respect it is submitted that Sir William's explanation leaves much to be desired. In particular, it seems right to point out that this country's ability to abolish unemployment during the last war and the present war - when the country's employment situation is determined, not by its economic situation, but by the demands on its man-power for the Armed Forces; when the country has to pay its way, not by its export trade, but by realising its foreign investments; when it is meeting half of its public expenditure by borrowing, and when it is carrying on under the generous Lease-and-Lend provisions of the U.S.A. - affords no sure foundation on which to base any estimate of what the unemployment figure will be when the war is over and this country, recovering from its war strain, has once again to depend, for its employing capacity, upon its ability to sell its goods in the world's markets. (63) Looking at the possible post-war situation, it would, we think, be foolhardy to assume that any international arrangements, whatever they may be, will enable this country to find a market for its goods irrespective of price, and that/ 200/B/3/2/C216/5/50